Vaginal Birth After Previous Caesarean Section - Fattah, Chro N.; Jalal, Hazha (Kurdistan Journal of Applied Research, 2017)
The proportion of women who attempt vaginal birth after prior cesarean delivery has decreased mainly because of the concern about safety. The purpose of this study is to observe maternal & neonatal outcomes in women delivered either by vaginal birth after caesarean section, elective repeat caesarean section or failed trial of labour. To design a definite protocol for selection of patient to achieve successful vaginal birth after caesarean (VBAC) section. A prospective observational study was set at Sulaimani Maternity Teaching Hospital/ Kurdistan region of Iraq, from first July 2013 to first July 2014. In which 200 pregnant women (with one prior caesarean section & singleton, term, cephalic presentation) were enrolled, followed up during labour & puerperium for maternal & neonatal complications. Data analysis was performed using the statistical software namely (SPSS version 20). Planned vaginal birth was successful in 63.4% of pregnant women, with the least maternal and neonatal complication, apart from 3rd degree perineal tear (2.3%) which was statistically significant (probability value < 0.001). In conclusion, the women who had successful vaginal birth after caesarean, had better result for the mother and neonate than failed trial of labour and those who had elective repeat caesarean section. Women with body mass index of < 30kg/m2, age <30 years, inter pregnancy interval >18months, non-recurrent cause of previous scar and estimated fetal weight of < 4kg, had more successful VBAC rate.